Evaluation of The Effect of Completeness of Inpatient Medical Records on Patient Safety Incidents at Kendari City Hospital - Sander, Tara; Sulistyowati, Yeny; Garnida, Aliefety Putu (Syntax Corporation Indonesia, 2026)
Medical records are official documents that contain comprehensive information about a patient’s health condition, including medical history, examination results, diagnoses, medical procedures, and therapies provided. Incomplete medical records can hinder communication among healthcare professionals and increase the risk of patient safety incidents. This research aimed to evaluate the effect of medical record completeness on patient safety incidents at Kendari City General Hospital. The research employed a mixed-method approach with a population of 6,026 patients and a sample of 110 documents. The independent variable was medical record completeness, while the dependent variable was patient safety incidents. Data were collected through reviews of electronic medical records (EMR) and analyzed using multiple linear regression. The results showed that the completeness of inpatient medical records did not have a significant effect on patient safety incidents (regression coefficient = –0.036; p = 0.261). Authentication and digital signatures were the only indicators that significantly influenced patient safety incidents (B coefficient = –0.346; p = 0.000). These findings indicate that inpatient medical record completeness is not the sole factor contributing to patient safety incidents. In the short term, hospitals need to strengthen authentication procedures and conduct routine audits; in the medium term, integrating EMR technology with real-time authentication alerts and training on record completeness should be implemented; and in the long term, hospitals may adopt a fully integrated digital authentication system within EMR equipped with Artificial Intelligence (AI)-based automated verification.